Pengaruh Arus Kas Operasi, Investasi, Pendanaan, dan Laba Bersih terhadap Return Saham pada Perusahaan Anggota IDXTECHNO di BEI - Evin Evin; Winda Evyanto (eCo-Buss, 2022)
This study aims to find out the effect of operating cash flow, investment cash flow, funding cash flow, and net income on stock returns. Using data from cash flow reports, profit reports, and share prices of IDX:TECHNO member companies listed on the Indonesia Stock Exchange 2018-2020. The financial aspect has a significant influence on the rate of return on a company's shares. If it manages to score good financial performance it will make a company's rate of return increase so that it benefits investors. Based on the results of the study, it was found that operating cash flow and investment cash flow had no effect on stock returns based on t test with a significant value > 0,05 while funding cash flow and profit had a positive and significant effect on stock returns based on t test with a significant value. < 0,05 and operating cash flow, investment cash flow, funding cash flow, and net income together have a positive and significant effect on stock returns based on F test with a significant value < 0,05. The conclusion from the research results is that investors who want to invest in the Indonesia Stock Exchange, especially in IDX: TECHNO member companies, should pay attention to the company's financial performance, this is because the existing research results show the effect of financial performance on stock returns.